Fibrinogen acts as a bridging molecule in the adherence of Staphylococcus aureus to cultured human endothelial cells. - Cheung, A L (1991)
The propensity of Staphylococcus aureus to cause acute endovascular infections during transient bacteremia is poorly understood. To examine the events leading to the attachment of staphylococci to endothelium, adherence assays were developed to study the role of blood factors in the mediation of staphylococcal adherence to cultured human umbilical vein endothelium in vitro. Results indicate that the preferential attachment of S. aureus to endothelial cells is mediated by fibrinogen adsorbed from plasma onto the endothelial surface. The binding is apparently specific because it could be blocked by goat anti-human fibrinogen antibody in a dose-dependent fashion while nonimmune goat IgG, mouse MAb against AG-1 (a platelet antigen found on the endothelial cell surface), nonspecific mouse MAb and rabbit antibodies to human vitronectin and fibronectin were not inhibitory. Our data also indicate that fibrinogen is a necessary but not the only blood constituent in the mediation of binding of S. aureus to endothelium. This was supported by the finding that fibrinogen alone, at a concentration equivalent to that in plasma, did not potentiate staphylococcal adherence as much as plasma while afibrinogenemic plasma reconstituted with fibrinogen did. Because fibrinogen is known to bind to endothelial cells, our data is consistent with the hypothesis that fibrinogen and additional plasma factor(s), possibly activated during inflammation, promote staphylococcal adherence to endothelium. In addition, the role of the fibrinogen binding receptor of S. aureus as an adherence factor to native endothelium is also suggested.